Gezi Park and EuroMaidan: social movements at the borders. Issue 1 (2nd January 2016) - Önal, Leyla
Abstract : Both Turkey and Ukraine are located at the external borders of the European Union (EU), and are seen as important partners of the EU, especially in terms of economic relations and strategic partnership. Both countries experienced en masse protest events in 2013: the Gezi Park protests and EuroMaidan, starting, respectively, in May 2013 and November 2013. Although these protests started initially for different reasons – the brutal eviction of a sit-in organized for protecting the trees in Taksim Gezi Park and the Ukrainian government's abandonment of EU trade agreement talks – and seem spatially, temporally and ideologically separate, they both include claims related to a "more just and transparent system". Such claims are not purely political and are closely linked to a social dimension, especially in terms of local and European space-making. This article aims to understand the importance of Gezi Park and EuroMaidan within the framework of new social movements in terms of space-making and the perception of human rights, democracy, justice, identitarian politics and consensual social relations as Euro-concepts or European ideals.